Analisis SCM : Studi Fenomenologi Pada Rumah Sakit Panti Wilasa Semarang - Lyna Rahardjo; Magdalena Nany; Setyo Budiadi (JRB-Jurnal Riset Bisnis, 2018)
It is not the strongest of the species that survives, nor the most intelligent that survives. It is the one that is the most adaptable to change. Change is done by management to continue the existence of a company or an organization in a dynamic environment. The objective of this research was to give empirical evidence about customers’ satisfaction, employees’ satisfaction and hospital’s position in strategic change matrix introduced by Black and Gregersen. Data came from 50 hospital’s patients and 50 hospital’s employees were analyzed by using strategic change matrix analysis. The results show that customers and employees were satisfied enough with the hospital’s management. The results also show that the hospital was lying on stage 1 in strategic change matrix introduced by Black and Gregersen.